Evaluation of Public Service Quality: Between Regulation and Reality - Ita Ulansari; Mufarrihul Hazin; Ima Widiyanah; Budi Purwoko (International Journal of Education, Language, and Religion, 2025)
In the context of sustainable development (Sustainable Development Goals/SDGs), improving the quality of public services is an important aspect to support Goal 16, "Peace, Justice, and Strong Institutions." This study aims to comprehensively evaluate the quality of public services at the Bojonegoro District Education Office, highlighting the gap between the expectations outlined in regulations and the reality of service practices at the service provider unit. The research was conducted at the Bojonegoro District Education Office using a qualitative case study approach to evaluate the quality of public services in government agencies. Data collection was carried out using observation, document analysis, and interviews with non-probability sampling—purposive sampling. The data analysis technique used was flow chart analysis according to Miles-Huberman, which includes data reduction, data display, and drawing conclusions/verification. In conducting the evaluation of public service quality, the framework of William N. Dunn was used, which includes criteria for assessing effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the data analysis indicate an improvement in the quality of public services at the Bojonegoro District Education Office, as reflected in the results of the community satisfaction survey and the assessment of compliance with public service delivery. However, based on the analysis of the evaluation results, it is necessary to formulate constructive policy recommendations for improving the quality of public services in the future to support the achievement of organizational goals.